2021
DOI: 10.3390/catal11060690
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effective Solvothermal Method to Synthesize Zn-Doped TiO2 Nanomaterials for Photovoltaic and Photocatalytic Degradation Applications

Abstract: Titanium dioxide (TiO2) is a commonly used wide bandgap semiconductor material for energy and environmental applications. Although it is a promising candidate for photovoltaic and photocatalytic applications, its overall performance is still limited due to low mobility of porous TiO2 and its limited spectral response. This limitation can be overcome by several ways, one of which is doping that could be used to improve the light harvesting properties of TiO2 by tuning its bandgap. TiO2 doped with elements, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…For antibacterial activities, zinc- and copper-doped TiO 2 nanoparticles have been reported. The results show that the doping of both the materials is considered an essential antibacterial agent, and strongly influenced photocatalytic degradation and antibacterial properties [ 28 , 29 ]. In addition, Polyvinylchloride coated with a combination of silver nanoparticles and zinc oxide nanowires also showed potential for antimicrobial applications [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For antibacterial activities, zinc- and copper-doped TiO 2 nanoparticles have been reported. The results show that the doping of both the materials is considered an essential antibacterial agent, and strongly influenced photocatalytic degradation and antibacterial properties [ 28 , 29 ]. In addition, Polyvinylchloride coated with a combination of silver nanoparticles and zinc oxide nanowires also showed potential for antimicrobial applications [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite all these benefits, as TiO 2 has a wide band gap (3.2 eV), its photocatalytic efficiency is less in removing pollutants under different light sources. Therefore, to enhance the photocatalytic activity of TiO 2 , researchers employed different processes like metal doping such as Ag, Mn, Cu, V, Mo, Cr, Fe, and Zn and non-metal doping such as P, C, N, S, and TiO 2 nanocomposites . Numerous studies have found that doping metal oxides with transition metals can improve the photocatalytic activity, owing to a shift in the absorption region from UV to visible light due to a change in their electronic structure .…”
Section: Introductionmentioning
confidence: 99%
“…Its development and the respective technological enhancement are crucial to address the emerging environmental problems associated with the current use of fossil fuels [1][2][3] as the proposed energy conservation/ storage devices shall be cost-effective, and more reliable with integrated generation of sources and reduced environmental impacts. [4][5][6][7][8] Moreover, an improved energy storage system is essential for the efficient utilization of solar, hydro, and wind energies. [9][10][11] Such energy storage devices could be used in various applications with specic requirements.…”
Section: Introductionmentioning
confidence: 99%